The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1158/1538-7445.am2020-1756
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1756: JBI-802, novel dual inhibitor of LSD1-HDAC6 for treatment of cancer

Abstract: Introduction: Lysine Specific Demethylase 1 (LSD1) is over-expressed in many cancers and down-regulation of LSD1 has been shown to effectively treat cancers by inducing re-expression of aberrantly silenced genes. Studies have shown that LSD1 may contribute to acute myelogenous leukaemia pathogenesis by inhibiting the normal pro-differentiative function of ATRA, paving the way for new combinatorial therapies for AML. In addition, LSD1 inhibition also leads to convertion of ‘cold' tumors to ‘hot' tumors by activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A successful example is JBI‐802, a first‐in‐class potent and selective dual inhibitor of LSD1 and HDAC6/8. Synergistic antitumor activity demonstrated in animal models 212 promoted a phase 1/2 CT for patients with advanced solid tumors that recently was opened (ClinicalTrials.gov identifier NCT05268666).…”
Section: Epigenetic Drugsmentioning
confidence: 99%
“…A successful example is JBI‐802, a first‐in‐class potent and selective dual inhibitor of LSD1 and HDAC6/8. Synergistic antitumor activity demonstrated in animal models 212 promoted a phase 1/2 CT for patients with advanced solid tumors that recently was opened (ClinicalTrials.gov identifier NCT05268666).…”
Section: Epigenetic Drugsmentioning
confidence: 99%
“…Very recently, JBI-802 has been identified by Jubilant Therapeutics Inc. as a dual LSD1/HDAC6/8 inhibitor, featuring nanomolar inhibition of the above three targets (IC 50 values: 50 nM (LSD1), 11 nM (HDAC6), and 98 nM (HDAC8)) and about 100-fold selectivity against other HDAC isoforms ( Sivanandhan et al, 2020 ). In hematological cancers (such as AML, chronic lymphocytic leukemia, acute megakaryocytic leukemia, Z-138 lymphoblast cells, multiple myeloma cells) as well as in solid tumors (small cell lung cancer (SCLC) and sarcoma cells) JBI-802 displayed huge antiproliferative effect.…”
Section: Lsd1 Inhibitorsmentioning
confidence: 99%
“…In hematological cancers (such as AML, chronic lymphocytic leukemia, acute megakaryocytic leukemia, Z-138 lymphoblast cells, multiple myeloma cells) as well as in solid tumors (small cell lung cancer (SCLC) and sarcoma cells) JBI-802 displayed huge antiproliferative effect. Functional tests for target engagement studies performed both in vitro and in vivo showed significant dose-dependent increase in CD11b, CD86 and GFI1b (markers of LSD1 inhibition) and tubulin acetylation (marker of HDAC6 inhibition) levels ( Sivanandhan et al, 2020 ). JBI-802 entered Phase 1/2 clinical trial for treatment of advanced and metastatic solid tumors ( Table 1 ).…”
Section: Lsd1 Inhibitorsmentioning
confidence: 99%
“…Sivanandhan et al. designed this novel dual inhibitor using computational chemistry approaches and demonstrated its efficacy in vitro against sarcomas and other hematological cancers ( 110 ) ( Table 1 ). Another example is Corin, a synthetic compound that inhibits both HDAC1 and LSD1 in the CoREST complex ( 111 ).…”
Section: Lsd1 In the Clinicmentioning
confidence: 99%